Artist as Owner Not Guarantor: The Art Market from the Artist's Point of View. (3rd April 2018) - Whitaker, Amy
Abstract : The events of 2016 in which the painter Peter Doig (b. 1959) was sued in US Federal Court for failing to authenticate an artwork for a speculative investor encapsulate a view of the art world from the perspective of collectors and not artists. This paper imagines what would happen if artists were to retain 10% equity in their work in the primary market, rather than receive resale royalties in the secondary market. This idea applies the Coase Theorem in economics, concerning the relationship of property rights, pricing, and trade. Accordingly, those equity shares could trade in a standalone marketplace well before an artwork was sold, providing patronage for artists and more diversifiable art fund structures for investors. Technological systems such as the blockchain (e.g. bitcoin) make such a system timely, by providing cheap accounting and automatic provenance. This proposal stands in stark contrast to much of the writing on resale royalties, which treats payments to artists as welfare or subsidy, or emphasizes a lack of enforceability. In fact, assigning equity shares to artists allows them to participate more accurately, from a free-market-economics standpoint, in the value that their work creates. This realignment of price and value could radically alter and also stabilize the art market in relation to both recent financial crises and the increasing financialization of art objects. Such a system has broad applications to the alignment of price and value in many other sectors of creative work, and beyond.